Asphalt mixture based on desulfurized rubber powder-nano palygorskite-steel slag powder composite modification and preparation method thereof
By using desulfurization glue powder, nano-sagite and steel slag powder in asphalt mixture, the disease problems of asphalt pavement under high and low temperature conditions are solved, the pavement performance and service life are improved, and environmental protection and economicality are achieved. Improved efficiency.
Patent Information
- Application Number
- CN202411110019.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-24
AI Technical Summary
Existing asphalt pavement is prone to brittle crust, softening, cracking, peeling, deformation and other diseases under extreme weather conditions of high and low temperatures, resulting in a shortening of the service life of the pavement. It is difficult for the existing technology to take into account both high and low temperature damage problems.
Using a composite modified asphalt mixture based on desulfurization glue powder, nano-paraffle and steel slag powder, the heat resistance, wear resistance and corrosion resistance of asphalt are improved through modification treatment, and improved agents and couplings are added during the preparation process. to form better interface bonding and dispersion, and improve the physical and mechanical properties and environmental sustainability of asphalt mixture.
It significantly improves the high-temperature stability, low-temperature crack resistance, water stability and fatigue resistance of asphalt mixture, extends the service life of the road surface, reduces road surface damage caused by cracks and water damage, and has a simple process and low cost, which is in line with Environmental protection requirements.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of road engineering materials, and in particular to an asphalt mixture based on composite modification of desulfurized rubber powder-nanopalyogorite-steel slag powder and a preparation method thereof. Background Art
[0002] With the rapid development of transportation, road construction has also been greatly developed. Asphalt pavement has become the most widely used pavement structure in China due to its advantages such as sufficient mechanical strength, smooth and comfortable driving, low vibration, no dust, low noise and easy maintenance. However, in actual application, due to the poor low and high temperature resistance of asphalt materials, when used in low temperature climate conditions in the north, the pavement is prone to brittle crusting, asphalt mixture bulges and loses the smoothness of the pavement; when used in the south where it is exposed to the sun for a long time, the asphalt mixture is easy to soften, and the pavement asphalt thickness is prone to unevenness, resulting in uneven pavement defects.
[0003] The increase in extreme weather conditions of high and low temperatures and the complexity of environmental conditions have led to serious road surface disease problems on many highway asphalt pavements after they were built and put into operation, such as cracking, peeling, deformation, etc. Such diseases have greatly shortened the service life of the pavement, causing many highways to enter the overhaul or renovation period ahead of schedule, resulting in a large amount of economic losses. The main technical means used to solve the disease problems caused by high and low temperatures in today's asphalt pavements is to apply road surface cooling coatings, etc., but such measures cannot simultaneously solve the damage caused by high and low temperatures to the pavement.
[0004] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0005] The present application provides an asphalt mixture based on composite modification of desulfurized rubber powder-nanopalyogorite-steel slag powder and a preparation method thereof, aiming to improve the road performance of the asphalt mixture while reducing high and low temperature diseases and water damage of the asphalt pavement.
[0006] According to one aspect of the present disclosure, there is provided an asphalt mixture based on a composite modification of desulfurized rubber powder-nanopalphyllite-steel slag powder, which is made of the following raw materials in parts by weight: 100 parts of mineral material, 3 to 7 parts of asphalt, 0.05 to 0.10 parts of desulfurized rubber powder, 0.06 to 0.18 parts of nanopalygorskite, 0.03 to 0.07 parts of steel slag powder, 0.015 to 0.028 parts of an improver, and 0.001 to 0.005 parts of a coupling agent.
[0007] In some embodiments of the present disclosure, the asphalt mixture is made of the following raw materials in parts by weight: 100 parts of mineral material, 4 to 6 parts of asphalt, 0.06 to 0.08 parts of desulfurized rubber powder, 0.12 to 0.15 parts of nano-palygorskite, 0.04 to 0.06 parts of steel slag powder, 0.018 to 0.021 parts of improver, and 0.003 to 0.005 parts of coupling agent.
[0008] In some embodiments of the present disclosure, the asphalt mixture is made of the following raw materials in parts by weight: 100 parts of mineral material, 4.4 parts of asphalt, 0.075 parts of desulfurized rubber powder, 0.129 parts of nano-palygorskite, 0.044 parts of steel slag powder, 0.019 parts of improver, and 0.0035 parts of coupling agent.
[0009] In some embodiments of the present disclosure, the asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, SBR modified asphalt, and fiber modified asphalt.
[0010] In some embodiments of the present disclosure, the coupling agent is a composite monoalkoxy titanate.
[0011] In some embodiments of the present disclosure, the improving agent is montmorillonite.
[0012] In some embodiments of the present disclosure, the mineral material consists of coarse aggregate, fine aggregate and mineral powder.
[0013] According to another aspect of the present disclosure, a method for preparing an asphalt mixture based on composite modification of desulfurized rubber powder-nanopalyogorite-steel slag powder is provided, comprising the following steps: (1) Raw material preparation: Prepare the raw materials according to the above weight ratio and set aside.
[0014] (2) Preparation of nano-palyosite modifier: Dilute the coupling agent with ethanol to a volume percentage concentration of 2-4%, then mix the nano-palyosite, the modifier, and the diluted solution of the coupling agent in a mass ratio of 0.8-1.2:0.033-0.037:0.09-0.13, and then stir at 80°C-85°C for 1-1.5 hours. Finally, dry and remove the anhydrous ethanol.
[0015] The modification of nano-palyorcsite by combining the improving agent montmorillonite with the coupling agent composite monoalkoxy titanate can give full play to the advantages of both: the interlayer structure adjustment of montmorillonite and the surface modification of the coupling agent can significantly improve the dispersibility of nano-palyorcsite in the asphalt matrix; the chemical bridge bonds formed by the coupling agent between the inorganic material and the organic material, as well as the interaction between montmorillonite and nano-palyorcsite, jointly enhance the interfacial bonding force between nano-palyorcsite and the organic matrix; the heat resistance, wear resistance, corrosion resistance, etc. of nano-palyorcsite are given or improved through the modification treatment.
[0016] (3) Preparation of desulfurized rubber powder and steel slag powder modifier: Dry the desulfurized rubber powder and steel slag powder at 110-130°C for 20-40 minutes and set aside.
[0017] Desulfurized rubber powder can improve the performance, optimize the road performance, and promote environmental protection and sustainability in asphalt mixtures: Desulfurized rubber powder can significantly improve the low-temperature ductility of asphalt, so that the modified asphalt mixture can still maintain good flexibility under low temperature conditions, reducing the brittle cracking of the road surface caused by temperature drop; due to the good combination between desulfurized rubber powder and asphalt and the improvement of the performance of modified asphalt, the modified asphalt mixture has higher durability and can withstand vehicle loads and environmental factors for a longer time; desulfurized rubber powder modified asphalt can reduce the production and processing temperature, reduce energy consumption, and improve construction and workability during processing. This makes it easier to spread and compact asphalt mixtures, improving construction efficiency and quality.
[0018] Steel slag powder has many positive effects in asphalt mixture. It not only improves the physical and mechanical properties of the mixture and optimizes road performance, but also promotes environmental protection and sustainable development: based on good mineral, mechanical properties and chemical stability, steel slag powder can significantly enhance the compressive strength and durability of asphalt mixture; the components in steel slag powder react chemically with asphalt, enhancing the adhesion between asphalt and aggregate, thereby improving the crack resistance of asphalt mixture; the porous and highly alkaline steel slag powder has very good adhesion to asphalt, which helps to improve the thermal stability and water stability of asphalt mixture; the addition of steel slag powder can significantly improve the resistance of asphalt mixture to water damage; after mixing steel slag powder with asphalt, it can form a tighter structure, improve the shear strength and deformation resistance of the mixture, and under high temperature conditions, this enhanced anti-rutting performance helps to maintain the flatness and stability of the road surface.
[0019] (4) Preparation of composite modified asphalt: Heat the base asphalt at a temperature of 140-180°C to melt it, first add the nano-palygorskite modifier, then add the desulfurized rubber powder modifier and steel slag powder modifier after shearing, stir for 50-70 minutes, and place it in an environment of 140-160°C to swell and develop for 20-40 minutes.
[0020] (5) Preparing a composite modified asphalt mixture: heating the mineral material to 170° C. to 185° C., and mixing and stirring the mineral material with the composite modified asphalt.
[0021] In some embodiments of the present disclosure, in the step (4), after the nano-palygorskite is added, the mixture is sheared at a shear rate of 1500-2500 r / min for 15-25 min, and then the desulfurized rubber powder and the steel slag powder are added in sequence and sheared at a shear rate of 4500-5500 r / min for 30-50 min.
[0022] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. In this application, the modified asphalt mixture using desulfurized rubber powder, nano-palygorskite and steel slag powder can significantly improve the physical and mechanical properties (enhanced strength and durability, improved stability), road performance (enhanced high temperature stability, low temperature crack resistance, water stability, rutting resistance and fatigue resistance of asphalt pavement) and environmental sustainability of the asphalt mixture: the good combination of desulfurized rubber powder and asphalt, as well as the reinforcing effect of nano-palygorskite and steel slag powder, jointly improve the crack resistance of the asphalt mixture and reduce the road damage caused by cracks; the addition of desulfurized rubber powder, nano-palygorskite and steel slag powder improves the shear strength and deformation resistance of the asphalt mixture, thereby enhancing its rutting resistance; the addition of nano-palygorskite and steel slag powder can significantly improve the water damage resistance of the asphalt mixture and reduce the road damage caused by rain erosion.
[0023] 2. The composite modified asphalt mixture provided in this application uses mineral materials, asphalt, desulfurized rubber powder, nano-palygorskite, steel slag powder, composite monoalkoxy titanate, and montmorillonite. The raw materials are widely available and are non-toxic and harmless. The preparation process is simple, the production process is pollution-free, the cost is low, and it has good economic benefits.
[0024] 3. The composite modified asphalt mixture provided in this application uses mineral materials, asphalt, desulfurized rubber powder, nano-palygorskite, and steel slag powder to carry out composite modification of asphalt, and utilizes the characteristics of inorganic nanoparticle nano-palygorskite, such as few surface energy defects, many unpaired atoms, and strong surface adsorption, so that it can better combine with the base asphalt, so that the modified asphalt has a larger destructive load.
[0025] 4. The modified nanopalygorskite of this application has a wavelength of 860 cm -1 、830cm -1 and 793cm -1 New absorption peaks are generated at the sites, and the groups have organophilicity, which can effectively improve the dispersibility of nano-palygorskite particles in organic solvents. Adding modified nano-palygorskite makes asphalt mixture have better high and low temperature performance, water damage resistance and fatigue resistance.
[0026] 5. After the composite modified asphalt mixture provided in this application is fused with the matrix asphalt, the specific network structure formed by the nano-palygorskite combined with the filling of desulfurized rubber powder and steel slag powder particles makes its structural stability better, and also makes the connection between the nano-palygorskite interface and the matrix asphalt smoother, thereby improving the overall performance of the composite modified asphalt (improving high temperature stability, low temperature crack resistance and fatigue resistance, etc.). DETAILED DESCRIPTION
[0027] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0028] Unless otherwise specified, the raw materials and auxiliary raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, detection methods and test methods involved are all conventional methods unless otherwise specified.
[0029] In the following embodiments, the asphalt mixture based on the composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder includes the following preparation steps: the raw materials are configured according to the weight ratio of 100 parts of mineral material, 3 to 7 parts of asphalt, 0.05 to 0.10 parts of desulfurized rubber powder, 0.06 to 0.18 parts of nanopalygorskite, 0.03 to 0.07 parts of steel slag powder, 0.015 to 0.028 parts of improver (montmorillonite), and 0.001 to 0.005 parts of coupling agent (composite monoalkoxy titanate).
[0030] (1) Preparation of nano-palyorcsite modifier: First, the coupling agent (composite monoalkoxy titanate, Yangzhou Yanyang New Material Technology Co., Ltd.) was diluted with ethanol to a concentration of 3%. Then, the nano-palyorcsite, the diluted coupling agent, and the improving agent (montmorillonite) were mixed evenly in a volume ratio of 1:0.035:0.11. The mixed solution was then heated and stirred at 85°C for 1.5 h. Finally, it was placed in a drying oven to dry and remove the ethanol to obtain the prepared nano-palyorcsite modifier.
[0031] (2) Preparation of desulfurized rubber powder modifier: Place the desulfurized rubber powder in an oven at 120°C and dry for 30 minutes for dehydration.
[0032] (3) Preparation of steel slag powder modifier: Place the steel slag powder in an oven at 120°C and dry for 30 minutes for dehydration.
[0033] (4) Preparation of composite modified asphalt: After the base asphalt is heated and melted at 160°C, nano-palygorskite is added first, and then the desulfurized rubber powder and steel slag powder are gradually added after being stirred evenly with a high-speed shearing machine. After stirring for 60 minutes, the mixture is placed in an environment of 150°C for swelling and development for 30 minutes. The preparation of the composite modified asphalt is completed.
[0034] (5) Preparation of composite modified asphalt mixture: The mineral material heated to 180° C. and the composite modified asphalt obtained in step (4) are mixed and stirred uniformly according to a conventional method to obtain a composite modified asphalt mixture.
[0035] The shearing process in step (4) is as follows: firstly, nano-palygorskite is added and sheared for 20 minutes at a shear rate of 2000 r / min, and then desulfurized rubber powder and steel slag powder are added and sheared for 40 minutes at a shear rate of 5000 r / min.
[0036] Example 1: An asphalt mixture based on composite modification of desulfurized rubber powder-nanopalyogorite-steel slag powder is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 3 parts of SBS asphalt, 0.05 parts of desulfurized rubber powder, 0.06 parts of nano-palygorskite, 0.03 parts of steel slag powder, 0.015 parts of improver (montmorillonite), and 0.001 parts of coupling agent (complex monoalkoxy titanate).
[0037] Example 2: An asphalt mixture based on a composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made of the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 4 parts of coal tar, 0.06 parts of desulfurized rubber powder, 0.09 parts of nanoopalphyrite, 0.04 parts of steel slag powder, 0.018 parts of an improver (montmorillonite), and 0.002 parts of a coupling agent (composite monoalkoxy titanate).
[0038] Example 3: An asphalt mixture based on a composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made of the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5 parts of road petroleum asphalt, 0.07 parts of desulfurized rubber powder, 0.12 parts of nano-palygorskite, 0.05 parts of steel slag powder, 0.021 parts of an improver (montmorillonite), and 0.003 parts of a coupling agent (composite monoalkoxy titanate).
[0039] Example 4: An asphalt mixture based on a composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5.5 parts of PE modified asphalt, 0.075 parts of desulfurized rubber powder, 0.135 parts of nanoopalphyrite, 0.055 parts of steel slag powder, 0.023 parts of an improver (montmorillonite), and 0.0028 parts of a coupling agent (composite monoalkoxy titanate).
[0040] Example 5: An asphalt mixture based on composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made of the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 6 parts of SBR modified asphalt, 0.08 parts of desulfurized rubber powder, 0.15 parts of nanoopalphyrite, 0.06 parts of steel slag powder, 0.025 parts of improver (montmorillonite), and 0.004 parts of coupling agent (composite monoalkoxy titanate).
[0041] Example 6: An asphalt mixture based on composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made of the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 4.4 parts of fiber-modified asphalt, 0.075 parts of desulfurized rubber powder, 0.129 parts of nanoopalphyrite, 0.044 parts of steel slag powder, 0.019 parts of improver (montmorillonite), and 0.0035 parts of coupling agent (composite monoalkoxy titanate).
[0042] Example 7: An asphalt mixture based on a composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 7 parts of road petroleum asphalt, 0.09 parts of desulfurized rubber powder, 0.18 parts of nano-palygorskite, 0.07 parts of steel slag powder, 0.028 parts of an improver (montmorillonite), and 0.0045 parts of a coupling agent (composite monoalkoxy titanate).
[0043] Example 8: An asphalt mixture based on composite modification of desulfurized rubber powder-nanopalphyrite-steel slag powder is made of the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 6.5 parts of SBS modified asphalt, 0.10 parts of desulfurized rubber powder, 0.165 parts of nanoopalphyrite, 0.065 parts of steel slag powder, 0.027 parts of improver (montmorillonite), and 0.005 parts of coupling agent (composite monoalkoxy titanate).
[0044] Comparative Example 1: A common asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material and 3 parts of SBS asphalt.
[0045] The asphalt mixtures obtained in Examples 1-8 and Comparative Example 1 were subjected to road performance tests, and the test items included a high temperature rutting test, a low temperature beam bending test (-10°C), a freeze-thaw splitting test, and a water immersion Marshall test to test the road performance of the composite modified asphalt mixture of the present invention, and compared and analyzed with a common asphalt mixture without adding a modifier. The test results are shown in Table 1 below.
[0046] Table 1 Asphalt mixture road performance test .
[0047] As can be seen from Table 1, the dynamic stability of the composite modified asphalt mixture is much greater than that of the ordinary asphalt mixture (Comparative Example 1), indicating that the high-temperature rutting resistance of the composite modified asphalt mixture is stronger than that of the ordinary asphalt mixture; the maximum flexural strain of the composite modified asphalt mixture is much greater than that of the ordinary asphalt mixture, indicating that the toughness and ductility of the composite modified asphalt mixture are stronger than those of the ordinary asphalt mixture; the residual stability and splitting strength ratio of the composite modified asphalt mixture are greater than those of the ordinary asphalt mixture, indicating that the low-temperature crack resistance and water stability of the composite modified asphalt mixture are stronger than those of the ordinary asphalt mixture.
[0048] The composite modified asphalt mixture of the present application meets the relevant requirements of the Ministry of Transport's standard JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction". Its high temperature stability, low temperature crack resistance, water stability and other indicators are significantly higher than those of ordinary asphalt mixtures, indicating that the composite modified asphalt mixture of the present application has excellent road performance.
[0049] The present application has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the spirit of the inventive concept, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. An asphalt mixture based on composite modification of desulfurized rubber powder-nanopalyogorite-steel slag powder, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 3-7 parts of asphalt, 0.05-0.10 parts of desulfurized rubber powder, 0.06-0.18 parts of nano-palygorskite, 0.03-0.07 parts of steel slag powder, 0.015-0.028 parts of improver and 0.001-0.005 parts of coupling agent.
2. The asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 4-6 parts of asphalt, 0.06-0.08 parts of desulfurized rubber powder, 0.12-0.15 parts of nano-palygorskite, 0.04-0.06 parts of steel slag powder, 0.018-0.021 parts of improver and 0.003-0.005 parts of coupling agent.
3. The asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 4.4 parts of asphalt, 0.075 parts of desulfurized rubber powder, 0.129 parts of nano-palygorskite, 0.044 parts of steel slag powder, 0.019 parts of improver and 0.0035 parts of coupling agent.
4. The asphalt mixture according to claim 1, characterized in that: The asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, SBR modified asphalt, and fiber modified asphalt.
5. The asphalt mixture according to claim 1, characterized in that: The coupling agent is a composite monoalkoxy titanate.
6. The asphalt mixture according to claim 1, characterized in that: The improving agent is montmorillonite.
7. The composite modified asphalt mixture according to claim 1, characterized in that: The mineral material consists of coarse aggregate, fine aggregate and mineral powder.
8. A method for preparing the asphalt mixture according to claim 1, characterized in that: The steps include: (1) preparing the raw materials according to the weight proportions as described in claim 1; (2) Preparation of nano-palygorskite modifier: dilute the coupling agent with ethanol to a volume percentage concentration of 2-4%, then mix the nano-palygorskite, the modifier, and the diluted solution of the coupling agent in a mass ratio of 0.8-1.2:0.033-0.037:0.09-0.13, and then stir at 80°C-85°C for 1-1.5 hours, and finally dry and remove the ethanol; (3) Preparation of desulfurized rubber powder and steel slag powder modifier: Dry the desulfurized rubber powder and steel slag powder at 110-130°C for 20-40 minutes and set aside; (4) Preparation of composite modified asphalt: Heat the base asphalt at a temperature of 140-180°C to melt it, first add the nano-palygorskite modifier, then add the desulfurized rubber powder modifier and the steel slag powder modifier after shearing, stir for 50-70 minutes, and then place it in an environment of 140-160°C to swell and develop for 20-40 minutes; (5) Preparing a composite modified asphalt mixture: heating the mineral material to 170° C. to 185° C., and mixing and stirring the mineral material with the composite modified asphalt.
9. The preparation method according to claim 8, characterized in that: In the step (4), after adding the nano-palygorskite, shearing is performed at a shear rate of 1500-2500 r / min for 15-25 min, and then desulfurized rubber powder and steel slag powder are added in sequence and sheared at a shear rate of 4500-5500 r / min for 30-50 min.
Citation Information
Cited By
Asphalt mixture and preparation method thereof
CN122541137A
An asphalt mixture and a method for producing the same
CN122541137B
